DISSIPATION KINETICS AND DIETARY RISK OF EMAMECTIN BENZOATE IN GRAPES USING LIQUID CHROMATOGRAPH-MASS SPECTROMETRY - BANKA KANDA KISHORE REDDY*, K. BHUVANESWARI, A. SUGANTHI, M. PARAMASIVAM; P. GEETHA (The Journal of Research ANGRAU, 2021)
The study aim was to find out how emamectin benzoate disappears and is leaving terminal residues in grapes. Modified QuEChERS method was developed, validated in Liquid Chromatograph-Mass Spectrometry (LC-MS) and used for estimating the residues of emamectin benzoate. The method linearity was good (R2 > 0.99) and its Limit of Quantification (LOQ) was determined as 0.01 mg/kg. Relative standard deviation (RSD) was found to be less than 5% for the average recoveries obtained, ranged from 99.77 to 102.44 %. Emamectin benzoate half-life in grapes at single (11 g a.i/ ha) dose (X) and double (22 g a.i/ha) dose (2X) was 1.11 and 1.22 days, respectively. The calculated hazard quotient (HQ) was found evident and cause negligible risk in terms of health hazard to consumers due to intake of emamectin benzoate residues through grapes at both studied doses.